Additive method based on laser shock
Through laser impact processing technology, metal foils hit the substrate under the action of laser shock wave, solving the problems of narrow material selection and many defects in traditional additive manufacturing technology, and achieving efficient and excellent quality metal additive manufacturing.
Patent Information
- Application Number
- CN202411931771.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Traditional additive manufacturing technology based on alloy powder cladding has problems such as narrow material selection range and many printing defects.
Using laser impact processing method, the laser beam is irradiated in a direction perpendicular to the metal foil, so that the metal foil hits the substrate under the action of laser shock wave, realizing the additive bond between the metal foil and the substrate.
The close combination between solid metal materials is achieved, the efficiency and quality of metal additive manufacturing is improved, the product has excellent tensile strength and elongation, and the scope of material selection is broadened and defects are reduced.
Smart Images

Figure CN119589118A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of additive manufacturing, and in particular to an additive method based on laser shock. Background Art
[0002] Metal additive manufacturing technology is a highly forward-looking and innovative manufacturing route that can play an important role in many key industries such as consumer products, biomedical devices, automotive parts, defense weapon development, building materials, microelectronics industry and space technology.
[0003] Among the existing metal additive manufacturing technologies, laser shock peening-assisted additive manufacturing has become a highly-regarded technical route. This method mainly uses alloy powder as the processing material and combines laser shock peening with other equipment (selective laser melting or laser powder bed melting) to achieve the purpose of alternating forming and strengthening.
[0004] However, traditional additive manufacturing technology based on alloy powder cladding has problems such as a narrow material selection range and many printing defects. Summary of the invention
[0005] The purpose of this application is to provide an additive method based on laser shock to solve the above problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions:
[0007] A laser impact-based additive method, comprising: using a laser impact processing method, irradiating a laser beam perpendicular to a metal foil onto a metal foil coated with a sacrificial layer, so that the metal foil impacts a substrate under the action of a laser shock wave, and additively combining the metal foil with the substrate through the impact action; wherein the material of the substrate comprises metal; the angle between the metal foil and the substrate is 5-55°; in the laser impact processing method, the energy density of the laser is 4-15 GW / cm 2 .
[0008] According to an embodiment of the present application, the distance between the metal foil and the substrate is 1-10 cm.
[0009] According to an embodiment of the present application, the material of the metal foil includes at least one of titanium alloy, aluminum alloy, copper, and steel;
[0010] The material of the substrate includes any one of titanium alloy, aluminum alloy, copper and steel.
[0011] According to an embodiment of the present application, the speed at which the metal foil impacts the substrate is 200-2000 m / s.
[0012] According to an embodiment of the present application, the thickness of the metal foil is 10-2000 μm.
[0013] According to an embodiment of the present application, the material of the sacrificial layer is a polymer or a metal;
[0014] The thickness of the sacrificial layer is 50-200 μm.
[0015] According to an embodiment of the present application, a constraint layer is provided on a side of the sacrificial layer away from the metal foil, and the constraint layer is tempered glass or a water flow layer.
[0016] According to an embodiment of the present application, the thickness of the constraining layer is 2-10 mm.
[0017] Compared with the prior art, the beneficial effects of this application include:
[0018] The method of the present application can promote a tight and firm bond between solid metal materials, thereby realizing efficient metal additive manufacturing. The additive manufacturing products prepared by the method of the present application have excellent tensile strength and elongation. In addition, the method of the present application has a wide range of applicability and can be flexibly applied to the processing of a variety of metal materials, effectively broadening the material selection range of traditional alloy powder cladding additive manufacturing technology, and significantly reducing the defects in traditional additive manufacturing technology, thereby improving the overall manufacturing quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0020] Figure 1 A diagram showing the relative positions of the metal foil and the substrate in the method of the present application;
[0021] Figure 2 The scanning electron microscope photograph and element distribution diagram of the cross-sectional microstructure of the multilayer 7075 aluminum alloy material prepared in Example 1;
[0022] Figure 3 This is a graph showing the mechanical tensile properties of the multi-layer 7075 aluminum alloy material prepared in Example 1;
[0023] Figure 4 This is a solid-state connection morphology image of dissimilar metals prepared in Example 2;
[0024] Figure 5 This is a structural diagram of the additive product prepared in Comparative Example 1;
[0025] Figure 6 This is a structural diagram of the additive product prepared in Comparative Example 2.
[0026] Description of reference numerals:
[0027] 100-metal foil, 200-substrate, 300-AM sample, 400-sacrificial layer, 500-constraint layer, α-angle between metal foil and substrate, A-laser beam, S-distance between metal foil and substrate. DETAILED DESCRIPTION
[0028] As used herein:
[0029] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0030] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a sentence of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that sentence; other elements are not excluded from the claim as a whole.
[0031] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0032] In these examples, parts and percentages are by mass unless otherwise indicated.
[0033] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0034] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0035] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0036] During the laser shock processing, the nanosecond laser first interacts with the sacrificial layer to generate a high-temperature and high-pressure plasma. The plasma expands rapidly, generating a shock wave with a pressure of up to GPa. This shock wave can act on the surface of the metal material, introduce residual compressive stress, and bring about a work hardening effect. At the same time, the shock wave generated by the laser can drive the material to a higher speed. The inventors have found that laser shock technology can reach the critical speed for achieving solid-state connection of materials and realize the connection of solid-state materials to solid-state materials.
[0037] This application provides an additive method based on laser shock, referring to Figure 1 , including: using a laser shock processing method, irradiating a laser beam A in a direction perpendicular to the metal foil 100 onto the metal foil 100 coated with a sacrificial layer 400, so that the metal foil 100 impacts the substrate 200 under the action of the laser shock wave, and realizing additive bonding of the metal foil 100 and the substrate 200 through the impact action, thereby obtaining an additive manufacturing sample 300; wherein the material of the substrate 200 includes metal; the angle α between the metal foil and the substrate is 5-55°; in the laser shock processing method, the energy density of the laser is 4-15GW / cm 2 .
[0038] The method of the present application can make solid metal materials closely bonded to each other, realize the additive manufacturing of metals, and the additive manufacturing products obtained by the method of the present application have excellent tensile strength and elongation. Moreover, the method of the present application is applicable to a variety of metal materials, improving the problems of narrow material selection range and many printing defects in the additive manufacturing technology of the traditional alloy powder cladding method.
[0039] According to some embodiments of the present application, before the metal foil is impacted with the substrate under the action of the laser shock wave, the method further includes: grinding the surface of the substrate with sandpaper (320 mesh to 2500 mesh) to remove roughness and surface defects. The ground substrate is then cleaned with alcohol and dried to better achieve a solid-state connection effect between the substrate material and the metal foil.
[0040] According to the embodiments of the present application, reference Figure 1 , the angle α between the metal foil and the substrate is 5-55°. This angle will directly affect the force direction and flying speed of the metal foil to obtain the best collision conditions. If the angle α between the metal foil and the substrate is too small, the metal foil will contact the substrate as a whole, leaving pores. If the angle α between the metal foil and the substrate is too large, the speed of the metal foil impacting is uneven, which will make the metal foil and the substrate material not welded firmly, affecting the connection performance of the welding material.
[0041] For example, the angle α between the metal foil and the substrate may be 5°, 10°, 15°, 20°, 25°, 30°, 35°, 40°, 45°, 50°, 55° or any value between 5-55°.
[0042] According to an embodiment of the present application, in the laser shock processing method, the energy density of the laser is 4-15 GW / cm 2 The energy of the laser beam determines the pressure of the plasma, which affects the speed of the metal foil and ultimately the quality of the solid-state connection. A higher laser energy density can produce a higher impact velocity. When the laser energy density is within the above range, the metal foil can have a higher impact velocity without damaging the substrate and the metal foil.
[0043] For example, the energy density of the laser can be 4 GW / cm 2 , 5GW / cm 2 , 6GW / cm 2 , 7GW / cm 2 , 8GW / cm 2 , 9GW / cm 2 、10GW / cm 2 、11GW / cm 2 、12GW / cm 2 、13GW / cm 2 、14GW / cm 2 、15GW / cm 2 Or 4-15GW / cm 2 Any value in between.
[0044] According to an embodiment of the present application, the distance S between the metal foil and the substrate is 1-10 cm.
[0045] For example, the distance S between the metal foil and the substrate may be 1 cm, 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, 7 cm, 8 cm, 9 cm, 10 cm or any value between 1-10 cm.
[0046] According to an embodiment of the present application, the material of the metal foil includes at least one of titanium alloy, aluminum alloy, copper, and steel;
[0047] The material of the substrate includes any one of titanium alloy, aluminum alloy, copper and steel.
[0048] According to an embodiment of the present application, the speed at which the metal foil hits the substrate is 200-2000 m / s. The metal foil hits the substrate material at a high speed under the action of the shock wave, thereby achieving a solid-state connection.
[0049] For example, the speed at which the metal foil impacts the substrate can be 200 m / s, 300 m / s, 400 m / s, 500 m / s, 600 m / s, 700 m / s, 800 m / s, 900 m / s, 1000 m / s, 1100 m / s, 1200 m / s, 1300 m / s, 1400 m / s, 1500 m / s, 1600 m / s, 1700 m / s, 1800 m / s, 1900 m / s, 2000 m / s or any value between 200-2000 m / s.
[0050] According to an embodiment of the present application, the thickness of the metal foil is 10-2000 μm. When the thickness of the metal foil is within the above range, the metal foil can maintain a good solid-state connection effect, thereby achieving a reliable connection. If the thickness of the metal foil is too small, it is easy to melt under laser impact. If the thickness of the metal foil is too large, it cannot obtain sufficient speed to hit the substrate, which is not conducive to the effect of solid-state connection.
[0051] For example, the thickness of the metal foil can be 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm, 900μm, 1000μm, 1100μm, 1200μm, 1300μm, 1400μm, 1500μm, 1600μm, 1700μm, 1800μm, 1900μm, 2000μm or any value between 10-2000μm.
[0052] The thickness of the metal foil can be adjusted according to the melting point of the metal material and the laser power. Metal materials with low melting points and lasers with high power density can perform solid-state welding on thicker metal foils. On the contrary, the welding effect may be affected if the foil is too thick or the laser power is too low.
[0053] According to the embodiments of the present application, reference Figure 1 The sacrificial layer 400 is located on the side of the metal foil 100 away from the substrate 200. The sacrificial layer 400 is made of a polymer or a metal, which is easy to generate high-temperature plasma. Further, the polymer can be a black organic tape, that is, a black tape.
[0054] The thickness of the sacrificial layer is 50-200 μm. The sacrificial layer is used to absorb part of the laser energy and generate plasma. The material and thickness of the sacrificial layer will directly affect the efficiency and impact effect of plasma generation.
[0055] For example, the thickness of the sacrificial layer may be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, or any value between 50-200 μm.
[0056] Through the interaction between the sacrificial layer and the laser beam, the high-temperature and high-pressure plasma generated drives the metal foil, causing the metal foil to hit the base material at an extremely high speed (200-2000m / s). When the metal foil and the base material collide at high speed, the material interface temperature rises, the surface oxide film breaks, and the elements diffuse with each other, thereby achieving solid-state metallurgical bonding between the metal foil and the base material.
[0057] According to the embodiments of the present application, reference Figure 1 A constraining layer 500 is provided on one side of the sacrificial layer 400 away from the metal foil 100 . The constraining layer 500 is used to limit the propagation direction of the shock wave formed after the plasma expansion so that it can only continue to propagate toward the direction of the substrate material.
[0058] According to some embodiments of the present application, the constraining layer is tempered glass or a water flow layer. When the constraining layer is made of the above materials, the constraining layer can have good light transmittance, thereby ensuring the propagation efficiency of the laser energy.
[0059] According to an embodiment of the present application, the thickness of the constrained layer is 2-10 mm. If the thickness of the constrained layer is too large, it will affect the transmission of laser energy. If the thickness of the constrained layer is too small, the limiting effect on the shock wave will be weakened.
[0060] For example, the thickness of the constraining layer may be 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm or any value between 2 and 10 mm.
[0061] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0062] Example 1
[0063] Embodiment 1 provides an additive method based on laser shock to achieve solid-state connection of the same refractory metals, specifically comprising:
[0064] In Example 1, the materials of the base material and the metal foil are both 7075 aluminum alloy, wherein the thickness of the base material is 1 mm, and the thickness of the printed metal foil is 20 μm. After the base material is polished with sandpaper, the polished base material and the metal foil are ultrasonically cleaned for 10 minutes to remove surface impurities to ensure the quality of the connection.
[0065] The metal foil and substrate were processed by laser shock processing. The angle between the metal foil and the substrate was adjusted to 35°, the distance between the metal foil and the substrate was 5 cm, the sacrificial layer was made of black tape, the thickness of the sacrificial layer was 80 μm, the constraint layer was made of tempered glass, and the thickness of the constraint layer was 3 mm. The laser energy density was selected to be 4.24 GW / cm 2 , the impact speed of the metal foil is 680m / s. After the first layer of metal foil is successfully connected, the entire weld is regarded as the base material, and another 7075 aluminum alloy sheet with a thickness of 30μm is added. Repeat the above steps to obtain a multi-layer solid-state connected aluminum alloy material with a thickness of 3mm. The additive product prepared in Example 1 is as follows Figure 2 As shown, Figure 2 (a) is a scanning electron microscope photograph of the cross-sectional microstructure of the multilayer 7075 aluminum alloy material prepared in Example 1, Figure 2 (b) is the element distribution diagram of the multilayer 7075 aluminum alloy material prepared in Example 1.
[0066] Depend on Figure 2 It can be seen that the structures of the refractory metals of each layer of 7075 aluminum alloy are tight. In addition, the multi-layer 7075 aluminum alloy material prepared in Example 1 was subjected to a tensile test to evaluate the connection strength and performance of the multi-layer 7075 aluminum alloy. The results are shown in FIG. Figure 3 As shown by Figure 3It can be seen that the tensile strength of the multilayer 7075 aluminum alloy material prepared in Example 1 is 264MPa, and the elongation reaches 13%. Compared with the tensile strength and elongation of 7075 aluminum alloy mentioned in the journal literature (PANIGRAHI SK, JAYAGANTHAN R. Effect of ageing on microstructure and mechanical properties of bulk, cryorolled, and roomtemperature rolled Al 7075alloy[J]. Journal of Alloy and Compounds, 2011, 509: 9609-9616), which are 618MPa and 6%, respectively, the elongation of the multilayer 7075 aluminum alloy material prepared in Example 1 is increased by 2.16 times. The bonding strength of the multilayer 7075 aluminum alloy material prepared in Example 1 is 28N.
[0067] Example 2
[0068] Embodiment 2 provides an additive method based on laser shock to achieve laminated additive manufacturing of dissimilar metal materials, specifically comprising:
[0069] In Example 2, the base material is titanium alloy, and the metal foils are 7075 aluminum alloy, brass, and pure iron, wherein the thickness of the base material is 1 mm, and the thicknesses of the metal foils (7075 aluminum alloy, brass, and steel) are 30 microns, 50 microns, and 30 microns, respectively. After the base material is polished with sandpaper, the polished base material and metal foil are ultrasonically cleaned for 10 minutes to remove surface impurities to ensure the quality of the connection.
[0070] The metal foil and substrate were processed by laser shock processing. The angle between the metal foil and the substrate was adjusted to 30°, the distance between the metal foil and the substrate was 5 cm, the sacrificial layer was made of black tape, the thickness of the sacrificial layer was 80 μm, the constraint layer was made of tempered glass, and the thickness of the constraint layer was 3 mm. The laser energy density was selected to be 7.6 GW / cm 2 , the impact speed of the metal foil is 830m / s. After the first layer of 7075 aluminum alloy foil is successfully connected, the entire weld is regarded as the base material, and a 50-micron thick brass sheet is added, and the above steps are repeated. Finally, a 30-micron thick steel sheet is added, and the above steps are repeated to obtain a multi-layer solid-state connection of dissimilar metal materials.
[0071] Figure 4 This is the solid-state connection morphology of dissimilar metals prepared in Example 2. Figure 4It can be seen that the structures of the refractory metal layers of the dissimilar metal prepared in Example 2 are tight. The bonding strength of the dissimilar metal prepared in Example 2 is 24N.
[0072] Comparative Example 1
[0073] The metal foil and substrate were processed by laser shock processing. The substrate material was titanium alloy, and the metal foil was 7075 aluminum alloy. The thickness of the substrate material was 1 mm, and the thickness of the metal foil material was 30 μm. The substrate material and the metal foil were ultrasonically cleaned for 10 minutes to remove surface impurities to ensure the quality of the connection. The angle between the metal foil and the substrate material was adjusted to 30°, the distance between the metal foil and the substrate was 5 cm, the material of the sacrificial layer was black tape, the thickness of the sacrificial layer was 80 μm, and the material of the constraint layer was tempered glass, and the thickness of the constraint layer was 3 mm. The laser energy density was selected to be 15.92 GW / cm 2 At this time, the impact speed of the metal foil is 1120m / s.
[0074] Figure 5 The structure diagram of the additive product prepared in Comparative Example 1 is as follows: Figure 5 It can be seen that the metal foil is separated from the base material, and the metal foil and the base material are not tightly connected. This may be due to the excessive laser energy density, which damages the metal foil and causes partial melting. The bonding strength of the additive product prepared in Comparative Example 1 is only 12N.
[0075] Comparative Example 2
[0076] The metal foil and substrate were processed by laser shock processing. The substrate material was titanium alloy, and the metal foil was 7075 aluminum alloy. The thickness of the substrate material was 1 mm, and the thickness of the metal foil material was 30 μm. The substrate material and the metal foil were ultrasonically cleaned for 10 minutes to remove surface impurities to ensure the quality of the connection. The angle between the metal foil and the substrate material was adjusted to 30°, the distance between the metal foil and the substrate was 8 cm, the material of the sacrificial layer was black tape, the thickness of the sacrificial layer was 100 μm, and the material of the constraint layer was tempered glass, and the thickness of the constraint layer was 3 mm. The laser energy density was selected to be 3.5 GW / cm 2 , the impact speed of the metal foil is 400m / s. In addition, a 7075 aluminum alloy sheet with a thickness of 30μm is added. Repeat the above steps to obtain a multi-layer solid-state connected aluminum alloy material.
[0077] Figure 6 This is a structural diagram of the additive product prepared in Comparative Example 2. Figure 6It can be seen that the metal foil is not tightly connected to the base material, and cracks appear in each layer of the metal foil. This may be caused by the low laser energy density. The bonding strength of the additive product prepared in Comparative Example 2 is only 8N.
[0078] Comparative Example 3
[0079] The metal foil and substrate were processed by laser shock processing. The substrate material was titanium alloy, and the metal foil was 7075 aluminum alloy. The thickness of the substrate material was 1 mm, and the thickness of the metal foil material was 30 μm. The substrate material and the metal foil were ultrasonically cleaned for 10 minutes to remove surface impurities to ensure the quality of the connection. The angle between the metal foil and the substrate material was adjusted to 0°, the distance between the metal foil and the substrate was 8 cm, the material of the sacrificial layer was black tape, the thickness of the sacrificial layer was 80 μm, and the material of the constraint layer was tempered glass, and the thickness of the constraint layer was 3 mm. The laser energy density was selected to be 7.6 GW / cm 2 , the impact speed of the metal foil is 830m / s. In addition, a 7075 aluminum alloy sheet with a thickness of 30μm is added again. Repeat the above steps to obtain a multi-layer solid-state connected aluminum alloy material. In Comparative Example 3, the structure between each layer of 7075 aluminum alloy refractory metal is looser than that in Example 2, and the tight bonding strength of the additive product prepared in Comparative Example 3 is only 17N.
[0080] Comparative Example 4
[0081] The metal foil and substrate were processed by laser shock processing. The substrate material was titanium alloy, and the metal foil was 7075 aluminum alloy. The thickness of the substrate material was 1 mm, and the thickness of the metal foil material was 30 μm. The substrate material and the metal foil were ultrasonically cleaned for 10 minutes to remove surface impurities to ensure the quality of the connection. The angle between the metal foil and the substrate material was adjusted to 60°, the distance between the metal foil and the substrate was 10 cm, the material of the sacrificial layer was black tape, the thickness of the sacrificial layer was 80 μm, and the material of the constraint layer was tempered glass, and the thickness of the constraint layer was 3 mm. The laser energy density was selected to be 7.6 GW / cm 2 , the impact speed of the metal foil is 830m / s. In addition, a 7075 aluminum alloy sheet with a thickness of 30μm is added. Repeat the above steps to obtain a multi-layer solid-state connected aluminum alloy material. In Comparative Example 4, the structure between each layer of 7075 aluminum alloy refractory metal is looser than that in Example 2, and the bonding strength of the additive product prepared in Comparative Example 4 is only 14N.
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0083] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A laser shock-based additive method, characterized in that: include: A laser impact processing method is adopted to irradiate a laser beam perpendicular to the direction of the metal foil onto the metal foil coated with the sacrificial layer, so that the metal foil impacts the substrate under the action of the laser shock wave, and the metal foil and the substrate are additively bonded by the impact action; The material of the substrate includes metal; the angle between the metal foil and the substrate is 5-55°; in the laser impact processing method, the energy density of the laser is 4-15GW / cm 2 .
2. The laser shock additive method according to claim 1, characterized in that: The distance between the metal foil and the substrate is 1-10 cm.
3. The laser shock-based additive method according to claim 1, characterized in that: The material of the metal foil includes at least one of titanium alloy, aluminum alloy, copper and steel; The material of the substrate includes any one of titanium alloy, aluminum alloy, copper and steel.
4. The laser shock additive method according to any one of claims 1 to 3, characterized in that: The metal foil hits the substrate at a speed of 200-2000 m / s.
5. The laser shock-based additive method according to claim 1, characterized in that: The thickness of the metal foil is 10-2000 μm.
6. The laser shock-based additive method according to claim 1, characterized in that: The material of the sacrificial layer is polymer or metal.
7. The laser shock-based additive method according to claim 1, characterized in that: The thickness of the sacrificial layer is 50-200 μm.
8. The laser shock-based additive method according to claim 6, characterized in that: A constraining layer is provided on a side of the sacrificial layer away from the metal foil.
9. The laser shock-based additive method according to claim 8, characterized in that: The constraining layer is tempered glass or a water flow layer.
10. The laser shock-based additive method according to claim 8 or 9, characterized in that: The thickness of the constraining layer is 2-10 mm.
Citation Information
Patent Citations
Device and method for preventing shock wave reflection during laser shock forming
CN106944525A
Method and system for composite additive manufacturing of layered heterogeneous parts
CN116352092A
Material and working method for build up by laser beam
JP1997285884A
Laser beam machining apparatus and method for manufacturing metal-joining material
JP2008049365A
Overlay Material For Laser Shock Peening
US20170225266A1